Peran Sekolah Dalam Menanggulangi Perilaku Bullying - Ma’rufah, Rosidatul; Pristiwiyanto, Pristiwiyanto (Program Studi Pendidikan Agama Islam, 2021)
Bullying is not a new thing for everyone. Bullying can occur at any age, but begins to increase in late elementary school, peaks in middle school, and declines at the college level. The existence of differences between groups and individuals is one factor in the occurrence of bullying. Physical, psychological, social conditions, from economy, religion, culture, race and gender are some of the factors that trigger bullying. Bullying is the biggest obstacle for children to self-actualize. Therefore, it takes handling and coordination from various parties such as parents, teachers, school principals, and employees. In this study, researchers tried to analyze and reveal about bullying prevention with a focus on the problem. How is the role of schools in tackling bullying behavior in children? This study uses a qualitative research method with a case study approach. Research informants are the Principal, Student Affairs, and BP Teachers. Data collection techniques used are interviews and documentation. The data analysis technique used Miles and Huberman analysis. Test the validity of the data by triangulation and adequacy of references. The results of this study indicate that the role of schools in tackling bullying in children is as a mediator, by providing socialization, as an analyst of child development, by paying attention to children's academic achievements and also paying attention to children's backgrounds, as character building, with the rules that will make children character discipline.